2008
DOI: 10.4238/vol7-2gmr412
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death in salivary glands of Drosophila arizonae and Drosophila mulleri

Abstract: ABSTRACT. Programmed cell death (PCD) in insect metamorphosis assumes a great diversity of morphology and controlling processes that are still not well understood. With the objective of obtaining information about the PCD process, salivary glands of Drosophila arizonae and D. mulleri were studied during larval-pupal development. From the results, it can be concluded that the type of the PCD that occurs in these organs is morphologically typical of apoptosis (formation of apoptotic nuclei, followed by fragmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The accumulation of clumps of condensed chromatin frequently attached to the inner surface of the nuclear membrane has been reported to be one of the most common morphological indicators of ongoing apoptosis (Kerr et al 1972;Wyllie 1980). Moreover, Ianella et al (2008) have reported that the lysosomal bodies around the nuclei tend to degrade even before fusing with the nuclei. The staining of PV tissues in the present investigation also agrees with these findings.…”
Section: Discussionmentioning
confidence: 98%
“…The accumulation of clumps of condensed chromatin frequently attached to the inner surface of the nuclear membrane has been reported to be one of the most common morphological indicators of ongoing apoptosis (Kerr et al 1972;Wyllie 1980). Moreover, Ianella et al (2008) have reported that the lysosomal bodies around the nuclei tend to degrade even before fusing with the nuclei. The staining of PV tissues in the present investigation also agrees with these findings.…”
Section: Discussionmentioning
confidence: 98%
“…Apoptosis is identified by morphological changes like condensation of cytoplasm and chromatin, breakdown of nuclear membrane, membrane blebbing and, in epithelial cells, loss of membrane polarity and disruption of cell junction proteins (Jänicke et al 1998;Atencia et al 2000;Ianella et al 2008). The canonical apoptotic pathway is evolutionarily conserved in invertebrates as well as in vertebrates (Aravind et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In D. variabilis and B. microplus , cell death is induced by apoptosis [5–8, 37, 38]. Our study showed that the apoptosis in salivary glands occurred at 3–4 days after attachment, which differs from that in R. sanguineus [9].…”
Section: Discussionmentioning
confidence: 79%